Study of Electrostatics and Transport Properties of Multigate Graded Nanowire Channel MOSFETs. (4th May 2016) - Khosru, Quazi D. M.; Khan, Saeed Uz Zaman; Datta, Kanak
Abstract : In this work, we have studied the electrostatics and ballistic transport characteristics of a multigate MOSFET structure with axially composition graded InGaAs channel. Wave-function penetration and other quantum mechanical effects were considered, along with the effects of strain on the graded heterojunction. Schrödinger and Poisson's equations were solved numerically using FEM method. Furthermore, we have studied effects of doping and depth variation of the graded layers on the threshold voltage and inversion gate capacitance of the device. The transport performance parameters extracted from the simulation revealed excellent on and off state transport performance of the graded device with an on-off current ratio of 10 7, Drain Induced Barrier Lowering of 43.79 mV/V, Subthreshold Swing of 61.37 mV/dec.